2021
DOI: 10.1016/j.ebiom.2021.103568
|View full text |Cite
|
Sign up to set email alerts
|

Baseline iron status and presence of anaemia determine the course of systemic Salmonella infection following oral iron supplementation in mice

Abstract: Background: Iron deficiency anaemia (IDA) is a major health concern. However, preventive iron supplementation in regions with high burden of infectious diseases resulted in an increase of infection related morbidity and mortality. Methods: We fed male C57BL/6N mice with either an iron deficient or an iron adequate diet. Next, they received oral iron supplementation or placebo followed by intraperitoneal infection with Salmonella Typhimurium (S.Tm). Findings: We found that mice with IDA had a poorer clinical ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 82 publications
(104 reference statements)
1
16
0
Order By: Relevance
“…In patients with an active infection, AI is actually a defense strategy of the body against invading microbes to restrict iron availability for pathogens also termed as "nutritional immunity" [234,235]. Therefore, treatment of AI in these patients, specifically with iron supplementation, not only promotes pathogen growth with increased virulence but also impairs the host immune response against pathogens [236][237][238][239]. There are three established therapies for the treatment of AI: iron replacement therapy, treatment with erythropoiesis-stimulating agents (ESAs) and red blood cell transfusion [2].…”
Section: Established Treatments Of Anemia Of Inflammationmentioning
confidence: 99%
“…In patients with an active infection, AI is actually a defense strategy of the body against invading microbes to restrict iron availability for pathogens also termed as "nutritional immunity" [234,235]. Therefore, treatment of AI in these patients, specifically with iron supplementation, not only promotes pathogen growth with increased virulence but also impairs the host immune response against pathogens [236][237][238][239]. There are three established therapies for the treatment of AI: iron replacement therapy, treatment with erythropoiesis-stimulating agents (ESAs) and red blood cell transfusion [2].…”
Section: Established Treatments Of Anemia Of Inflammationmentioning
confidence: 99%
“…The quantitative real-time PCR was carried out as described elsewhere ( Hoffmann et al., 2021 ). In brief, total RNA isolation was prepared using acid guanidinium thiocyanate-phenol-chloroform extraction with peqGOLD Tri-Fast™ (Peqlab).…”
Section: Methodsmentioning
confidence: 99%
“…Protein extraction and Western blotting were performed as described previously ( Hoffmann et al., 2021 ). The following antibodies were used: a rabbit FPN antibody [1:2000; Eurogentec, custom made ( Petzer et al., 2020 )], a mouse TFR1 antibody (1:1000; Sigma Cat# SAB4300398), a rabbit FT antibody (1:500; Sigma), a rabbit NGAL antibody (1:1000 Abcam, ab63929), a rabbit NRF2 antibody (1:1000, Abcam, ab31163), and a rabbit actin antibody (1:500; Sigma Cat# A2066).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies revealed that catecholate siderophore synthesis is not required to cause mouse typhoid indicating that requirement of iron during growth in extraintestinal sites might differ from the intestinal milieu in murine models ( Benjamin et al, 1985 ; Tsolis et al, 1996 ; Cunrath and Bumann, 2019 ). Oral supplementation of iron in mice with iron deficiency anemia increased the iron saturated transferrin fraction and led to overgrowth of STm in the liver and spleen ( Hoffmann et al, 2021 ). This overgrowth of STm was directly related to the ability to acquire iron mediated partly by catecholate siderophores (enterobactin, salmochelin) and FeoABC.…”
Section: Introductionmentioning
confidence: 99%
“…This overgrowth of STm was directly related to the ability to acquire iron mediated partly by catecholate siderophores (enterobactin, salmochelin) and FeoABC. Overall, data suggested the functional redundancy of the high affinity iron acquisition systems of STm in certain conditions, such as an imbalance of host’s iron homeostasis ( Hoffmann et al, 2021 ). All the evidence above suggests that there is a molecular arms race for iron between pathogens and the host which can decide the clinical outcome.…”
Section: Introductionmentioning
confidence: 99%